Out of sight: chronic kidney diseases among diabetic patients attending care and follow up. Findings from pastoralist health facilities of Southern Ethiopia - Israel, Eskinder; Borko, Ushula Deboch; Mota, Kuma; Tesfaw, Mihret; Feleke, Tihun; Abraham, Awoke; Akako, Bereket; Samuel, Beniyam; Aynalem, Amdehiwot (Frontiers in Public Health, 2024)
Background In Ethiopia, the prevalence of chronic kidney disease (CKD) among the adult population ranges to 19.1%. The disease's impact has increased in low-resource settings due to a lack of knowledge about the condition and its risk factors. Diabetes is one of the numerous causes of CKD. Despite this, little was known in Ethiopia, particularly in the study area. This study aimed to identify the determinants of CKD among diabetic patients enrolled in care and follow up at pastoralist health facility of Jinka General Hospital (JGH), Southern Ethiopia, 2023. Methods An institutional-based cross-sectional study design was conducted among 626 diabetic patients recruited through a systematic random sampling. Data was collected using a structured interviewer-administered questionnaire and entered into Epi data version 7.2 and then exported to the Statistical Package for Social Sciences (SPSS) version 25 for further analysis. Bivariate and multivariate logistic regression analyses were conducted to find eligible variables for the later analysis. Variables with p < 0.25 at bivariate logistic regression were selected for multivariate logistic regression analysis. The variables with p < 0.05 at the multivariate analysis were taken as statically significant in the final model. Results The prevalence of CKD was 2.7% (95% CI: 1.12–6.01%). Place of residence (AOR: 4.84; 95% CI: 1.51–15.40), presence of hypertension (AOR: 5.69; 95% CI: 1.58–20.51) and family history of CKD (AOR: 6.20; 95% CI: 1.40–15.49) were factors associated with CKD among diabetes patients. Conclusion The prevalence found in this study was low when compared with the local studies. Provision of health education to diabetic patients on preventative measures such as physical exercise is cost-effective approach. Factors associated with CKD among diabetics can be significantly mitigated by strengthening the existing NCDs prevention packages in the study area particularly and in Ethiopia generally.